Inhibition of Mouse Urinary Bladder Carcinogenesis by A double dagger ai Fruit (Euterpe oleraceae Martius) Intake - Fragoso, Mariana F. [UNESP]; Prado, Monize G. [UNESP]; Barbosa, Luciano [UNESP]; Rocha, Noeme Sousa [UNESP]; Barbisan, Luis Fernando [UNESP] (Springer, 2012)
A double dagger ai, fruit from Euterpe oleraceae Martius, is consumed in natura and in a variety of beverages and food preparations and possesses several potential antioxidant compounds. In a first study for anticarcinogenicity screening, male Swiss mice (n = 20/per group) were chemically-induced to urothelial bladder carcinogenesis for 10 weeks and received a standard diet or a standard diet containing 2.5 and 5 % spray-dried a double dagger ai pulp (AP) for 10 weeks. At week 20, the incidence of simple and nodular hyperplasia and the incidence and multiplicity of transitional cell carcinoma (TCC) were evaluated. In a second study for antigenotoxicity screening, male Swiss mice (n = 6/per group) were fed standard diet or standard diet containing 5 % AP for three weeks. Urothelial cell suspensions were obtained and challenged with H2O2 for induction of DNA damage and analyzed by comet assay. Overall, dietary 5 % AP reduced TCC incidence and multiplicity (p = 0.019 and p = 0.015, respectively) and tumor cell proliferation and p63 expression (p = 0.02 and p = 0.007, respectively), Furthermore, the group fed the 5 % AP presented a significant reduction (p < 0.01) in DNA damage induced by H2O2, a notable oxidant agent. The results suggest that the spray-dried a double dagger ai pulp used here inhibits the TCC development in male Swiss mice, probably due to its potential antioxidant action.
Keywords: Acai (Euterpe oleraceae Martius); Urinary bladder carcinogenesis; Cancer prevention; DNA damage